THE INFLUENCE OF FAMILY ENVIRONMENT ON CHILDREN'S ACADEMIC ACHIEVEMENT - Mudzakir Mudzakir; Cynthia Petra Haumahu; Sunanto Sunanto; Al-Amin (Adisam Publisher, 2025)
This study aims to analyze the relationship between family environment and children's academic achievement through literature analysis method. The results showed that there is a significant relationship between a supportive family environment and children's academic achievement. Emotional support, characterized by recognition of children's efforts, confidence building, and providing a safe space for learning, plays an important role in children's academic motivation. In addition, parents' active involvement in education - including checking homework, attending school meetings and providing learning resources at home - plays a role in improving academic achievement. A conducive learning environment at home, filled with reading materials, clear expectations about education and structured study habits, also supports children's cognitive development and academic achievement.